1973
DOI: 10.1111/j.1365-3180.1973.tb01265.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF MINIMUM SOIL TEMPERATURE ON DIFFERENTIAL DISTRIBUTION OF CYPERUS ROTUNDUS AND C. ESCULENTUS IN THE UNITED STATES*

Abstract: Tbe response of tubers to low temperatures was investigated to gain insight into a physiological basis for the differential distribution oi'CyPerus esculentus L. (yellow nuUedge) and C. rotundus L. (purple nutsedge) in the United States. Only C. esculentus tubers survived the winter of 1968-69 in the field at Urbana, Illinois. Less than 10% oiC. rotundus tubers survived at 2^0 for 12 weeks, whereas more than 95% of C. esculentus tubers survived this treatment. Exposures to -2''C for 4 h or longer killed 50% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

1975
1975
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
1
19
0
2
Order By: Relevance
“…Only 8% of the yellow nutsedge 'G' tubers were viable after the winter. These responses to cold agree with other research on differences in tuber survival between purple and yellow nutsedges (20). In addition, these data show intraspecific differences within the yellow nutsedges in the tuber response to cold.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Only 8% of the yellow nutsedge 'G' tubers were viable after the winter. These responses to cold agree with other research on differences in tuber survival between purple and yellow nutsedges (20). In addition, these data show intraspecific differences within the yellow nutsedges in the tuber response to cold.…”
supporting
confidence: 91%
“…Differences in response to the cold can explain the differential distribution of these two species (20 The polar lipids from leaf extracts were isolated by TLC on plates developed in petroleum ether-diethyl ether-ethanolamine (58:30:12). In this system, the polar lipids remained at the origin, whereas the pigments moved to the solvent front.…”
mentioning
confidence: 99%
“…Daily soil mean temperatures during the coldest month in the surveyed area remain between 3 o C and 6 o C (Boletín Agrometeorológico, 1988Agrometeorológico, , 1989Agrometeorológico, ,1991Agrometeorológico, , 1992. Even though temperatures are not as low as those reported by Stoller (1973) as limiting for species of nutsedge distribution in the USA, they make difficult the survival of tubers of purple nutsedge under field conditions, specially of those wintering near the soil surface and more exposed to frosts.…”
Section: Surveyed Area County Lim Itsmentioning
confidence: 84%
“…Stoller (1973) found that tubers of purple nutsedge did not survive soil temperatures of 2 o C during 12 weeks, while tubers of yellow nutsedge survived after receiving the same treatment. Daily soil mean temperatures during the coldest month in the surveyed area remain between 3 o C and 6 o C (Boletín Agrometeorológico, 1988Agrometeorológico, , 1989Agrometeorológico, ,1991Agrometeorológico, , 1992.…”
Section: Surveyed Area County Lim Itsmentioning
confidence: 95%
“…Entretanto, esse método de controle só deve ser realizado nos meses em que não ocorre precipitação pois seis dias após a aração, se fosse dada condição para que a tiririca germinasse, 13,7% dos tubérculos ainda estariam viáveis e apenas dezesseis dias após, nenhum tubérculos seria viável (Day & Russell, 1955) O maior problema em utilizar esse controle é a necessidade de operações muito freqüentes e que demandam tempo e dinheiro (Victória Filho, 1985). Além disso, segundo Smith & Mayton (1942) (Smith & Mayton, 1942) mas estes já foram observados até a profundidade de 0,40 m (Stoller, 1973). Bhardwaj & Verma (1968) A tiririca apresenta forte dominância apical e embora esta seja o principal fator que controla a dormência do tubérculo, a umidade do solo, a luz, o teor de oxigênio e a temperatura influenciam o processo de emissão de brotações.…”
Section: Aspectos Relativos à Tiriricaunclassified